Examining job satisfaction burnout and reality shock amongst newly graduated nurses - ERGÜN, YASEMİN (ELSEVIER SCIENCE BV, 2012)
This study has been conducted on 347 nurses with a maximum of two years of professional experience working at Ministry of Health Training and Research hospitals in Istanbul. This study aimed to investigate job satisfaction, burnout and reality shock amongst new graduated nurses. Data has been collected using questimmaire including socio-demographic characteristics of nurses, reality shock and affecting factors, Minnesota Occupational Satisfaction Scale and the Maslach Burnout Inventory. It has been found that 78,2% of nurses perceive the early periods of their career as difficult, 72,9% report that their job expectations are not met and therefore 52,2% stated that they do not plan to choose this profession again, whereas 42,4% think of quitting their job after the first two months of employment. In conclusion nursing schools and hospital administrations should give place to organizational and administrative regulation to make nurses' transition to the profession more straightforward. (C) 2012 Published by Elsevier Ltd.
Keywords: Burnout; Job Satisfaction; Newly Graduated Nurse; Reality Shock